Endocannabinoid system modulation for visceral abdominal pain in inflammatory bowel disease and irritable bowel syndrome: A protocol for systematic review and meta-analysis [version 2; peer review: 2 approved] - Rebecca M. Lane; Declan P. McKernan; Siobhain M. O'Mahony; Laurence J. Egan; David P. Finn; Brian E. McGuire (HRB Open Research)
Visceral Pain is a common debilitating symptom of inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS). The endocannabinoid system (ECS) is a prime target for alleviation of visceral pain, given its important role in both gastrointestinal physiology and pain. We will conduct a systematic review of randomised controlled trials (RCTs) of cannabis, cannabinoids, cannabis-based medicines (CBMs), and other ECS modulators for patients with IBD and IBS, comparing any preparation of cannabis, any cannabinoid, CBM, or other pharmacological modulator of the ECS (any dose, by any route of administration), with any control (placebo, or pharmacological / psychological / dietary intervention). We will search CENTRAL, MEDLINE, PubMed, EMBASE, and Web of Science databases, as well as the WHO International Clinical Trials Registry Platform and ClinicalTrials.gov Trials Registries, together with reference checking and citation searching, following PRISMA guidelines. Our objectives are to evaluate the benefits and harms of pharmacological modulation of the ECS for visceral abdominal pain in patients with IBD or IBS, compared to placebo or other interventions. The primary outcomes will be the proportion of people with (a) at least a 30% reduction and (b) at least a 50% reduction in pain. Secondary outcomes will include any change in pain intensity, physical and emotional functioning, fatigue and sleep measures, quality of life, gastrointestinal disease or symptom severity, and adverse effects. We will assess risk of bias in the RCTs using the Cochrane Risk of Bias 2 tool. Where there are sufficient data that are directly comparable, we will conduct meta-analyses of the results for each outcome. We will use the GRADEpro GDT tool to assess certainty of evidence for each outcome. This review will synthesise the available evidence regarding all types of ECS modulation for the treatment of visceral abdominal pain and its related comorbidities in IBS and IBD patients.